2014
DOI: 10.1039/c3cc48532c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cellular uptake of amphiphilic gold nanoparticles with ester functionality

Abstract: Gold nanoparticles (AuNPs) coated with ester-headed or ether-headed PEG ligands were synthesized. Ester-headed AuNPs, but not ether-headed, were transferred from the organic phase (CH2Cl2) to the alkali aqueous phase, indicating that the hydrolysis of the ester moiety triggered the phase transfer of the AuNPs. We found that AuNPs with ester-headed ligands (ester-AuNPs) were internalized into HeLa cells at a greater level than were ether-headed AuNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…27,28 We have previously demonstrated that thiolated-PEG ligands with a terminus consisting of a short alkyl chain provide AuNPs (10 nm in a diameter) with an amphiphilic property and facilitate the phase transfer of AuNPs from aqueous to organic solvents. 29,30 Stellacci et al…”
Section: Introductionmentioning
confidence: 98%
“…27,28 We have previously demonstrated that thiolated-PEG ligands with a terminus consisting of a short alkyl chain provide AuNPs (10 nm in a diameter) with an amphiphilic property and facilitate the phase transfer of AuNPs from aqueous to organic solvents. 29,30 Stellacci et al…”
Section: Introductionmentioning
confidence: 98%
“…The similar nanoparticle cell studies have shown that the particle clusters are uptaken by the cells via endocytosis. 58 The gold concentrations added to the cells were determined by ICP-MS and the results were summarized in Table S2 (ESI † ). The internalization of the 3 nm Den–AuNPs was the lowest, despite having the highest concentration in the original nanoparticle solution.…”
Section: Resultsmentioning
confidence: 99%
“…Niikura and coworkers demonstrated that an esterase-catalyzed hydrolysis of ester moieties can be used as to enhance the cellular uptake of amphiphilic AuNPs [76]. 10 nm AuNPs were functionalized with ester or ether-headed amphiphilic PEG ligands which enable NPs to dissolve both of polar and nonpolar solvents through systematic conformational changes (Fig.…”
Section: Engineering Responsive Biological Interactionsmentioning
confidence: 99%
“…(d) Esterase-induced cell internalization of AuNPs. Reprinted with permission from [76,77]. Figure 10d is based on information obtained in the report.…”
Section: Figurementioning
confidence: 99%